The Effect of Whole Wheat and White Breads on Serum Lipid Profile, Malondialdehyde, and C-Reactive Protein in Over-Weight and Obese Patients with Coronary Stent - Razieh Khoramnazari; Mousa Salehi; Javad Kojuri (International Journal of Nutrition Sciences, 2017)
Background: Observational studies showed that intake of whole-grain is associated with a reduced risk of coronary heart disease, hypertension, hyperlipidemia. However, only a few dietary intervention trials have investigated the effect of whole-grain consumption on health outcomes. So we aimed to examine the effect of whole wheat vs. white bread on serum lipid profiles, malondialdehyde (MDA); and C-reactive protein (CRP) in overweight and obese patients with coronary stent. Methods: In a randomized, single-blind, parallel trial, 80 participants who had stent and body mass index (BMI)≥25 were divided into two groups. Intervention group consumed 150 g of whole-wheat bread daily accompanied with a low-calorie diet and the control group consumed 150 g of white-wheat bread as well as a low-calorie diet. The intervention was continued for 12 weeks. Outcomes such as BMI, lipid profile, MDA, high-sensitivity (hs)-CRP, blood pressure, waist and hip circumferences were evaluated at baseline and end of the study. Results: whole- bread diet in comparison with white diet could significantly reduce weight, waist and hip circumferences, BMI, cholesterol, Low Density Lipoprotein (LDL), systolic blood pressure and hs-CRP. No significant differences were visible regarding lipid profile. No significant differences were noted between the two diets for triglyceride and High Density Lipoprotein (HDL) levels. Conclusion: The present results suggest that whole bread can significantly reduce oxidative and inflammatory marker level and several cardiovascular risk factors among overweight or obese patients with coronary stent.